2017
DOI: 10.1016/j.tibs.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A New View into the Regulation of Purine Metabolism: The Purinosome

Abstract: Other than serving as building blocks for DNA and RNA, purines metabolites provide a cell with the necessary energy and cofactors to promote cell survival and proliferation. A renewed interest in how purine metabolism may fuel cancer progression has uncovered a new perspective into how a cell regulates purine need. Under cellular conditions of high purine demand, the de novo purine biosynthetic enzymes cluster near mitochondria and microtubules to form dynamic multi-enzyme complexes referred to as purinosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
361
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 429 publications
(406 citation statements)
references
References 89 publications
13
361
0
2
Order By: Relevance
“…Similar “metabolons”, defined as “supramolecular complexes of sequential metabolic enzymes and cellular structural elements” [119], have been observed in other systems, such as the tricarboxylic acid cycle [120], the purinosome [121], dhurrin biosynthesis [122], and steroid biosynthesis [123]. Identifying the functions of such metabolon organization remains an active area of research with multiple hypotheses.…”
Section: The Coq Biosynthetic Complexmentioning
confidence: 95%
“…Similar “metabolons”, defined as “supramolecular complexes of sequential metabolic enzymes and cellular structural elements” [119], have been observed in other systems, such as the tricarboxylic acid cycle [120], the purinosome [121], dhurrin biosynthesis [122], and steroid biosynthesis [123]. Identifying the functions of such metabolon organization remains an active area of research with multiple hypotheses.…”
Section: The Coq Biosynthetic Complexmentioning
confidence: 95%
“…The cellular level of purines is maintained by coordinated actions of two pathways: the salvage pathway and the de novo biosynthesis pathway (for review, see Pedley and Benkovic 2017). The salvage pathway produces purines by recycling degraded bases in a single enzyme-catalyzed reaction (Murray 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, the salvage pathway is responsible for controlling the basal cellular purine level. Under conditions with higher purine demands such as active cell growth, the de novo biosynthesis pathway plays a dominant role in increasing purine synthesis (Pedley and Benkovic 2017). It has been reported that the regulatory capacity of the de novo biosynthesis is greater than that of the salvage pathway (Yamaoka et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…94,95 Collectively, the formation of purinosomes, which indicates the upregulation of de novo purine biosynthesis, has significantly advanced our understanding of the regulatory mechanisms of de novo purine biosynthesis in human cells. 9698 …”
Section: Nucleotide Biosynthesismentioning
confidence: 99%